Nastajanje standardov o netesnosti sistemov in naprav - Pregelj, Andrej (Vakuumist, 1997)
There is an increased number of products and technologies where vacuum tightness of vessels and tubes is of main importance. Their greater or minor tightness assures good and appropriate maintenance of over or under pressure. Critical points where leak can be expected with great possibility are usually as folows: fittings, demountable connections, gaskets, welded and soldered joints, defects in material, etc. Due to more and more pretentious requirements regarding the products quality (ISO 9000), in practice we come across with present regulations and standards which include also leak testing methods among which the main procedures are connected with vacuum technique. Regarding to relatively to scarce knowledge in this field at users and to the fact this sphere has not been treated by ISO yet, the European standard organisation (CEN) prepares in the frame of nondestructive testing also the chaptures on leak tightness. The contribution represents the basics of leak detection and the actual state of the CEN drafts.
Keywords: vakuumska tehnika; tesnjenje; standardi; netesnost